Unity certified programmer : exam guide : expert tips and techniques to pass the Unity certification exam at the first attempt - Walker, Philip (Packt Publishing, 2020)
This exam guide will take you from basic C# programming through the process of downloading, installing, and understanding how Unity works and prepare for your Unity exam. You will go through the core objectives of what is expected for the Unity exam and also have some fun on the way by creating a side-scrolling shooter game using Unity.